(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Currently strangulated hernia accounts for up to 7% of acute surgical diseases of the abdominal organs. At the same time, diagnostic errors in the preoperative period reach up to 10%, and in the hospital up to 8%. If you pay attention to the frequency of complications, this figure in the postoperative period is reached up to 30% and death, unfortunately, is observed up to 6% of cases. When referring to the emergency department, during examination or transportation, there is a spontaneous reduction of the strangulated inguinal hernia in up to 18% of cases, which complicates the tactics of the surgical solution of the situation.